2021
DOI: 10.1111/desc.13109
|View full text |Cite
|
Sign up to set email alerts
|

Language and socioemotional development in early childhood: The role of conversational turns

Abstract: This study examines the role of language environment (number of conversational turns) in the development of socioemotional competencies between 18 and 30 months. The language environment of 43 infants and their social‐emotional competencies were measured at 18 months and again at 30 months. Multiple regressions showed a significant contribution of turns at 18 months on socioemotional competencies at 30 months, controlling for their initial levels, child vocalizations, maternal warmth, and social risk. Cross‐la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Previous studies have shown that the number of turn-takings between child and parent in particular predicts future language outcomes [ 92 ]. Associations between number of words and conversational turns and socio-emotional skills one year later were also shown based on LENA [ 93 ]. Using the LENA devices in the AChild study is expected to provide further insights into influences of parental language and turn-taking on both the child’s social–communicative development and the family’s mental health.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the number of turn-takings between child and parent in particular predicts future language outcomes [ 92 ]. Associations between number of words and conversational turns and socio-emotional skills one year later were also shown based on LENA [ 93 ]. Using the LENA devices in the AChild study is expected to provide further insights into influences of parental language and turn-taking on both the child’s social–communicative development and the family’s mental health.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, while the majority of LENA research to date has focused on counts of adult and child words, as well as an overall tally of parent‐child conversations through the course of a day, the current study suggests that more fine‐grained data about the frequency and speaker identity for individual conversational initiation between parent and infant yield insights into family dynamics and, importantly, show meaningful links with psychological parenting constructs. These findings highlight the value of extending the use of LENA‐extracted data to consider the quality of dyadic interaction (e.g., Gomez & Strasser, 2021 ). In line with these nuanced findings, in our future work we plan to examine the content of both the parent‐child conversations as well as the affective quality and coherence of speech‐sample descriptions (Demers et al., 2010 ; Sher‐Censor et al., 2018 ).…”
Section: Discussionmentioning
confidence: 73%
“…For example, coordinated parent-child turn-taking at 4 months of age predicts attachment security at 12 months of age (Jaffe is needed, these findings highlight the importance of parental mentalizing in the prenatal period for early family interactions. et al, 2001), while frequency of conversational turn-taking between parent and child at 18 months of age predicts quality of parent-child interaction during free-play at 30 months of age (Gomez & Strasser, 2021). Thus, in the current study LENA measures of parent-child conversations were our outcomes of interest.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Demonstrating the importance of caregiver-child interaction and child-directed speech in early childhood development, these results stress the critical finding that conversations and subsequent child vocalizations, may be more significantly important for early language ability than the sheer quantity of words heard by children. Recent literature on the home language environment supports this finding (Romeo et al, 2018;Ramírez et al, 2020;Gómez and Strasser, 2021), as conversations have emerged as the most critical aspect of language environments for a child's developmental trajectory.…”
Section: Discussionmentioning
confidence: 83%